Adiksi Game Online Mobile Legend Pada Anak - Ria Kustiyani (Jurnal Psikologi Terapan, 2019)
This study aims to describe the addictive behavior of the online game Mobile Legend in children and its effect on children's time management. The approach used in this research is a qualitative method, with a descriptive method. In this study, the subject under study was a 9 year old boy who had addiction to online games. Data collection was carried out using interview and observation techniques. The result of this research is that high addiction to Online Game Mobile Legend and Mobile Legend: Bang Bang greatly influences the time usage of the subject. Time that should have been used to gain knowledge was wasted because it was used to play the game Mobile Legend: Bang Bang.